PENGGUNAAN TEKNOLOGI AUGMENTED REALITY SEBAGAI MEDIA PENGENALAN JENIS MOBIL PADA SHOWROOM - Danida Abas Romadlon; Adam Sekti Aji (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
The number of complaints about the efficiency of time and distance to see and get information related to the goods you want to buy is a common problem among consumers. Especially when consumers want to buy a car where consumers have to take the time to go to the showroom before making sure to buy the desired product. To overcome the problems that often occur, an Augmented reality (AR) based application was created that serves to promote and introduce various types of cars. Augmented reality (AR) is a 3D-based technology that will create space for consumers to see various types of cars. The method used in this research is Marker Based. The design of this application begins with collecting car model data in the form of 3D assets that will be developed using Unity software. This application is expected to help consumers to reach various car models in detail without having to take the time to visit the showroom. This application has been proven successful in displaying 3D car objects graphically and equipped with voice explanations. Based on mobile device testing, 95% results were obtained for the success of application functionality. This application has been successfully run and functions Augmented reality (AR) technology well.